Strategi Politainment Akun X Anies Bubble dalam Periode Kampanye Pilpres 2024 - Pratiwi, Silvi; Wuriani, Nur Indah; Hasibuan, Anra Muliasih Sah Bakti; Rahardjo, Turnomo (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study examines the politainment strategy employed by the X account @aniesbubble in the 2024 Indonesian presidential election campaign. The account adopts a communication style inspired by K-Pop fandom, presenting Anies Baswedan as an idol-like figure to attract Generation Z voters. This research utilizes a qualitative approach with content analysis as the method. The study aims to analyze how the Anies Bubble account integrates the ten elements of politainment formulated by David Schultz into its posts during the 2024 presidential campaign. The findings indicate that @aniesbubble incorporates nine out of ten elements, such as engaging storytelling, emotional involvement, and media modernity, to enhance Anies Baswedan’s appeal—particularly in reshaping his image and mobilizing public support. However, certain elements, such as building future expectations and swaying swing voters, were less optimized, while the element of securing funding was not identified. This study concludes that the politainment strategy employed by @aniesbubble demonstrates the potential of an organic and culturally relevant approach in shaping political perceptions, with the ability to reach a broader audience in the digital era and improve politicians public image.